Risk Factors for Acute Exacerbation in Patients with COPD Group E in Ningbo: Risk Analysis of Irregular Review, Cardiovascular Complications, and Lung Function Decline - Qian Y; Sun C; Zhang L; Cai C; Sun M; Zhang J; Huang J; Ma H; Tan L; Zhao Y; Wang S; Lv D (International Journal of COPD)
Yang Qian,1 Chao Sun,1 Liang Zhang,2 Chenting Cai,1 Mengqing Sun,1 Jiaqian Zhang,1 Jian Huang,3 Hongying Ma,1 Lin Tan,1 Yun Zhao,1 Shanshan Wang,1 Dan Lv1 1The First Affiliated Hospital of Ningbo University, Ningbo, 315010, People’s Republic of China; 2Ningbo Municipal Center for Disease Control and Prevention, Ningbo, 315000, People’s Republic of China; 3School of Big Data and Software Engineering, Zhejiang Wanli University, Ningbo, 315100, People’s Republic of ChinaCorrespondence: Dan Lv, The First Affiliated Hospital of Ningbo University, 59 Liuting Street, Ningbo City, Zhejiang Province, People’s Republic of China, Email fylvdan@nbu.edu.cnObjective: To understand the high-risk factors for disease progression in patients in the chronic obstructive pulmonary disease (COPD) group E in Ningbo, and to explore the impact of and treatment on the prognosis of these patients.Methods: We retrospectively analyzed the clinical data of 101 COPD patients in terms of general demographics, physical baseline data, lung function, disease treatment, and prognosis and used crosstab analysis and logistic regression analysis to understand the characteristics of the population of patients at high risk of acute exacerbation of COPD (AECOPD) and the associated risk factors.Results: Univariate analysis demonstrated that frequent acute exacerbation (AE) in the COPD group E population was significantly associated with more severe airflow limitation, a lower FEF75%, higher mMRC scores, and irregular disease management (P< 0.05). Comorbid cardiovascular disease increased AE risk 4.138-fold (P< 0.05). Multivariate analysis confirmed that irregular disease review, cardiovascular comorbidity, and mMRC grades 3– 4 were risk factors (P< 0.05). Regular review reduced AE risk, while cardiovascular disease and mMRC grades 3– 4 increased the risk 8.802-fold and 12.327-fold, respectively.Conclusion: The severity of airflow restriction, instantaneous flow during forced exhalation of 75% of the lung capacity, cardiovascular disease complexity, higher mMRC scores, and irregular participation in intervention treatment were associated with disease deterioration in patients at high risk of AECOPD. Regular participation in standardized intervention management and treatment is a protective factor against worsening events in high-risk patients with AECOPD. These results may reduce medical resource utilization and AE frequency while improving quality of life, thereby informing evidence-based COPD management strategies and optimizing chronic disease care and resource allocation.Keywords: COPD, intervention management, risk factors, regular review, acute exacerbation, high risk